Fish complementarity is associated to forests in Amazonian streams - Bordignon, Carolina Rodrigues [UNESP]; Casatti, Lilian [UNESP]; Pérez-Mayorga, María Angélica [UNESP]; Teresa, Fabrício Barreto; Brejão, Gabriel Lourenço [UNESP] (FapUNIFESP (SciELO), 2015)
The functional structure of communities is commonly measured by the variability in functional traits, which may demonstrate complementarity or redundancy patterns. In this study, we tested the influence of environmental variables on the functional structure of fish assemblages in Amazonian streams within a deforestation gradient. We calculated six ecomorphological traits related to habitat use from each fish species, and used them to calculate the net relatedness index (NRI) and the nearest taxon index (NTI). The set of species that used the habitat differently (complementary or overdispersed assemblages) occurred in sites with a greater proportion of forests. The set of species that used the habitat in a similar way (redundant or clustered assemblages) occurred in sites with a greater proportion of grasses in the stream banks. Therefore, the deforestation of entire watersheds, which has occurred in many Amazonian regions, may be a central factor for the functional homogenization of fish fauna.
Keywords: Amazon forest; Conservation; Ecomorphology; Functional diversity; Habitat use